Electrical cardiometry during transition and short-term outcome in very preterm infants: a prospective observational study - Schwarz, Christoph; O’Toole, J. M.; Healy, D. B.; Panaviene, J.; Livingstone, V.; Dempsey, Eugene (European journal of pediatrics, 2024)
The purpose of this study is to evaluate the association of Electrical Cardiometry (EC)-derived cardiac output indexed to weight (CO) and its changes during the first 48 h in relation to adverse short-term outcome in very preterm infants. In this prospective observational study of preterm infants < 32 weeks gestational age (GA), the combined adverse outcome was defined as mortality or abnormal cranial ultrasound (any grade intracranial hemorrhage (ICH) or periventricular leukomalacia) within the first 2 weeks postnatally. Logistic regression models were used to investigate the association between median CO and outcome and mixed-effects models for the time trajectory of CO. In the absence of device-specific thresholds for low or high CO, no thresholds were used in our analysis. Fifty-three infants (median (IQR) GA 29.0 (25.4-30.6) weeks, birthweight 1020 (745-1505) g) were included in the analysis. Median CO was 241 (197-275) mL/kg/min for the adverse outcome and 198 (175-227) mL/kg/min for normal outcome (odds ratio (OR) (95% confidence interval (95% CI)), 1.01 (1.00 to 1.03); p = 0.028). After adjustment for GA, the difference was not significant (adjusted OR (95% CI), 1.01 (0.99 to 1.02); p = 0.373). CO trajectory did not differ by outcome (p = 0.352). A post hoc analysis revealed an association between CO time trajectory and ICH ≥ grade 2.